Pengaruh Inflasi Harga Minyak Dunia Terhadap Ekonomi Indonesia - Edy Soesanto; Citra Wahyuningrum; Muhammad Kahfi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Changes in global oil prices have been one of the main factors influencing the Indonesian economy for the last few decades. As one of the leading oil and gas producers in Southeast Asia, Indonesia is significantly affected by fluctuations in global oil prices and has a broad impact on various sectors of the domestic economy. This research explores the impact of changes in oil prices on Indonesia's trade balance, inflation, economic growth and fiscal policy. In addition, analysis is carried out at the micro level to understand the direct implications on key sectors, such as the transportation industry, manufacturing industry and energy sector